2000
DOI: 10.4049/jimmunol.164.2.580
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Th2 Responses by Peptide Analogues in a Murine Model of Allergic Asthma: Amelioration or Deterioration of the Disease Process Depends on the Th1 or Th2 Skewing Characteristics of the Therapeutic Peptide

Abstract: Allergen-specific CD4+ Th2 cells play an important role in the immunological processes of allergic asthma. Previously we have shown that, by using the immunodominant epitope OVA323–339, peptide immunotherapy in a murine model of OVA induced allergic asthma, stimulated OVA-specific Th2 cells, and deteriorated airway hyperresponsiveness and eosinophilia. In the present study, we defined four modulatory peptide analogues of OVA323–339 with comparable MHC class II binding affinity. These peptide analogues were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 50 publications
3
49
0
1
Order By: Relevance
“…Various OVA and FMD-V peptides have previously been used as immunogenic epitopes to define antigen presentation, the kinetics of peptide-MHC binding, and assess antibody responses of cattle and mice [3,4,7,11,17,22,31]. FMD-VP2 and VP4, for example, were both demonstrated to bind with high affinity to BoLA-DRB3*1101 and BoLA-DRB3*0201, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various OVA and FMD-V peptides have previously been used as immunogenic epitopes to define antigen presentation, the kinetics of peptide-MHC binding, and assess antibody responses of cattle and mice [3,4,7,11,17,22,31]. FMD-VP2 and VP4, for example, were both demonstrated to bind with high affinity to BoLA-DRB3*1101 and BoLA-DRB3*0201, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may not be surprising, since the peptides used in this study were ranked according to their binding affinity for the BoLA-DRB3*2703 molecule, alone. Other variables including, peptide degradation, binding affinity for the T-cell receptor, expression of co-stimulatory and adhesion molecules, T-cell receptor avidity, surface density of MHC class II-T-cell receptor complexes, cell-cycle and length of differentiation time have also been demonstrated to influence MHC class II-T-cell receptor mediated T-lymphocyte function [2,6,11,16,20,29,30]. Our initial interpretation of the decreased DNA synthesis in the FMD-VP4 (high binding) peptide-specific T-lymphocytes was that there might be a hole in the T-cell repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…In several clinical trials, however, it has been shown that, although some patients showed a reduction of airway symptoms and Th2-associated responses, Fel d I peptide immunotherapy elicited allergic symptoms and late asthmatic reactions in cat-allergic asthmatics (7,8). Moreover, we recently showed that in OVA-sensitized mice, s.c. immunotherapy with the immunodominant T cell epitope OVA 323-339 enhanced both airway hyperresponsiveness (AHR) 3 and eosinophilia upon OVA challenge (9), while an in vitro defined superagonistic analogue of this OVA 323-339 epitope had a beneficial effect (10).…”
Section: The Efficacy Of Immunotherapy In An Experimentalmentioning
confidence: 99%
“…The outcome of these forms of immunotherapy was related to the site of Ag-specific T cell activation, and the magnitude of the T cell response using an adoptive T cell transfer model (19). In this model, limited numbers of fluorescent labeled (CFSE) OVA 323-339 -specific DO11.10 T cells were transferred into naive BALB/c recipients, and T cell activation and division in various lymphoid organs were monitored at various days after immunotherapy with OVA, OVA 323-339 , or the peptide analogue of OVA 323-339 , OVA 336 E-A, which we defined previously as a superagonistic peptide with comparable MHC-binding affinity as OVA [323][324][325][326][327][328][329][330][331][332][333][334][335][336][337][338][339] , but more potent in the induction of T cell proliferation and Th1 cytokine induction in DO11.10 T cells in vitro (10).…”
Section: The Efficacy Of Immunotherapy In An Experimentalmentioning
confidence: 99%
See 1 more Smart Citation